Application project task scheduling using dolphin swarm technology - Baraa S. Mostafa; Firdews A. Alsalman (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Project task scheduling, which is part of software project management, has great importance in the success or failure of projects as 40% of projects are subject to failure due to poor planning and misuse of human resources, andthis greatly confirms that the wise decisions that are made at this stage leadto reduced Obstacles facing work and leading tosuccess. The work and decision-making is the responsibility of the project manager as he faces all the complexity and critical phases of this critical phase and deals with all its related processes which consist of defining the project tasks and assigning the employees responsible for each task and then preparing project plans. In this research we dealt with project scheduling using The smart dolphins warm algorithm, the project scheduling process is essential in the software engineering industry nowadays and the possibility of finding good solution swhich saves the software company a lot of time and money.